Tasybih, Isti'arah, Kinayah in Imam Ghazali's Poetry: A rhetorical analytical study - Rohmah, Adinda Maulida; Naf’an, Abdul Wahab (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The poetry of Imam Ghazali possesses a variety of rhetorical beauties. These beauties can be found in Imam Ghazali’s poetry contained in the book al-Mukhtarat asy-Syi’riyah lil Imam Abi Hamid al-Ghazali. This study aims to analyse the elements of balaghah within the branch of bayan, which encompasses three elements: tasybih, isti’arah, and kinayah. The study uses a descriptive qualitative method with a balaghah approach. The results of the study indicate that out of ten verses of poetry, there are four forms of tasybih, two forms of isti’arah, and two forms of kinayah. The forms identified include tasybih tamtsil, tasybih baligh, tasybih mursal mufasshol, tasybih mursal mujmal, isti’arah tasrihiyyah, isti’arah makniyyah, kinayah ‘an-shifah, kinayah ‘an-maushuf and each verse possesses profound meaning and a deep message. The results of this analysis demonstrate that the utilization of these elements of the science of bayan imparts aesthetic value and profound meaning to each verse. This analysis not only reveals the depth of meaning and aesthetic value but also uncovers moral and spiritual values. Consequently, this poem by Imam Ghazali is relevant for study as it exhibits a high level of linguistic aesthetics from the perspective of the science of balaghah.